Biomimetic synthesis of active stilbenolignan derivatives by oxidative coupling and acid-catalyzed polymerization - Chunsuo Yao; Mao Lin; Qingyun Yang (Elsevier, 2013)
Two new stilbenolignans and one novel lactone stilbenolignan with a seven-membered ring were biomimetically synthesized by an oxidative coupling reaction and acid-catalyzed polymerization with either isorhapontigenin and ferulic acid or sinapinic acid, respectively, as the starting materials. The structures of the stilbenolignans were defined using spectral analysis and their mechanisms of formation are discussed. Anti-oxidant and anti-inflammatory activities of the novel stilbenolignans were tested, and the lactone stilbenolignan was observed to exhibit potent anti-oxidant activity.